Predictive value of systemic immune-inflammation index in patients with diabetes mellitus: a systematic review and meta-analysis - Dong, Yujie; Tang, Maoyuan; Xu, Yanmei; Peng, Qiyan (Frontiers in Endocrinology, 2025)
BackgroundEmerging evidence suggests an association between the systemic immune-inflammation index (SII) and the prognostic outcomes in individuals diagnosed with diabetes mellitus (DM). However, existing research presents inconsistent findings.MethodsPubMed, Embase, Web of Science, and the Cochrane Library from their inception to December 9, 2024, were retrieved to identify studies that scrutinized the interaction between SII and prognostic outcomes in DM patients. Primary outcomes included diabetic nephropathy (DN), diabetic retinopathy (DR), all-cause mortality, cardiovascular mortality, peripheral artery disease(PAD), and kidney mortality. Data were analyzed using odds ratios (ORs) or standardized mean differences (SMDs) with 95% confidence intervals (CIs). To ensure the robustness of results and uncover any underlying sources of heterogeneity, sensitivity analyses and subgroup analyses were also carried out.ResultsFollowing a comprehensive literature search and screening, the meta-analysis incorporated 22 studies involving 85,796 patients. Categorical variable analysis revealed that elevated SII levels were correlated with a markedly increased risk of DN [OR = 1.94, 95% CI (1.02, 3.67), P = 0.04], all-cause mortality [OR = 1.38, 95% CI (1.14, 1.67), P = 0.001], and cardiovascular mortality [OR = 1.55, 95% CI (1.12, 2.16), P = 0.009] compared to those with lower SII levels. Furthermore, continuous variable analysis also indicated a significant link between SII levels and the incidence of DN [SMD = 4.56, 95% CI (1.44, 7.67), P = 0.004] and DR [SMD = 2.70, 95% CI (1.77, 3.64), P < 0.0001].ConclusionSII serves as a reliable and profoundly meaningful biomarker in forecasting prognostic outcomes and assessing mortality risks among DM patients. However, given the limited quantity and quality of the studies included, these findings remain to be further validated.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024575794.